2018
DOI: 10.31160/jotci2018;26(1)a0014
|View full text |Cite
|
Sign up to set email alerts
|

Implementing telemedicine in the initial care for ST-segment elevation myocardial infarction

Abstract: Background: In ST-segment elevation myocardial infarction, the need for early recanalization of the culprit artery, associated to the difficult access of the general population to medical services that provide such treatment, contribute to increased mortality in such patients. This is the rationale for implementing the LATIN project, acronym for Latin America Telemedicine Infarct Network, in areas characterized by high demographic density and difficult access to healthcare services. The objective of the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
3
5
0
2
Order By: Relevance
“…Telemedicine service interventions are emerging as an effective alternative model for improving secondary prevention of CAD. Most previous studies have focused on applied telemedicine services for cardiovascular diseases, such as ECG analysis of ST‐segment elevation myocardial infarction, wherein in‐hospital mortality reduced and the percentage of patients with door‐to‐balloon time lower than 60 min increased (Matsuda et al, ). In addition, results indicated that telemedicine monitoring in patients with repeat percutaneous coronary intervention or cardioversion for atrial fibrillation is more effective in identifying cardiac arrhythmia (Morguet, Kühnelt, Kallel, Rauch, & Schultheiss, ); Furthermore, when telemedicine services are provided, there is a reduction in hospital admission rate, length of stay and mortality in patients with chronic heart failure and higher quality of life scores (Lin et al, ; Wakefield et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Telemedicine service interventions are emerging as an effective alternative model for improving secondary prevention of CAD. Most previous studies have focused on applied telemedicine services for cardiovascular diseases, such as ECG analysis of ST‐segment elevation myocardial infarction, wherein in‐hospital mortality reduced and the percentage of patients with door‐to‐balloon time lower than 60 min increased (Matsuda et al, ). In addition, results indicated that telemedicine monitoring in patients with repeat percutaneous coronary intervention or cardioversion for atrial fibrillation is more effective in identifying cardiac arrhythmia (Morguet, Kühnelt, Kallel, Rauch, & Schultheiss, ); Furthermore, when telemedicine services are provided, there is a reduction in hospital admission rate, length of stay and mortality in patients with chronic heart failure and higher quality of life scores (Lin et al, ; Wakefield et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine service interventions are emerging as an effective alternative model for improving secondary prevention of CAD. Most previous studies have focused on applied telemedicine services for cardiovascular diseases, such as ECG analysis of ST-segment elevation myocardial infarction, wherein in-hospital mortality reduced and the percentage of patients with door-toballoon time lower than 60 min increased (Matsuda et al, 2018).…”
mentioning
confidence: 99%
“…Mortality due to STEMI in the in-hospital period was 8.3%, characterizing a significant reduction when compared to the mortality rates in the public service, which reached 26.1% 11 and 15.3%, 10 in 2009 and 2010, respectively. In the region studied the rate is estimated to be even higher, because of difficult access to thrombolysis − a fundamental approach which should be guaranteed.…”
Section: Discussionmentioning
confidence: 86%
“…Nonetheless, it is important to point out that the said service only had one large spoke facilitating allocation to the transport service. 10 The mean door-balloon time at the hub was 54.3±37.7 minutes, with a median of 46 minutes; however, not considering the reclassified patients as evolved infarction, it was 51±31.3 minutes with a median of 44 minutes. Such values are closed to the means of a similar study, 10 but based on literature, 9 there is still space for improvements, especially in the communication between transport teams and hubs teams, optimizing the cath labs, avoiding idleness, and making access of infarcted patients easier.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation